The Legal Concept of Ownership of Finance Lease Objects from the Perspective of Legal Certainty for the Lessor - M. Kholid Artha (Universitas Pelita Harapan, 2026)
Among various sources of capital financing for companies, whether for working capital or investment in production equipment, leasing has become a very popular option. This popularity is due to its straightforward process, quick approval, tax deductibility, and lack of collateral requirements. Despite the existence of Law No. 4 of 2023 on the Development and Strengthening of the Financial Sector and Minister of Finance Decree No. 1169 of 1991 on Leasing Activities, and OJK Regulation No. 35 of 2018 on the Implementation of Financing Company Business, there are no regulations governing the civil aspects of leasing that address the rights and obligations of the parties involved and the legal certainty protecting the lessor's ownership of leased goods. Existing regulations primarily address public and institutional aspects, leading to potential legal uncertainties in practice. The purpose of this research is to explore the legal concept of the lessor’s ownership of leased assets and the importance of establishing legal certainty in this context. This research employs a normative juridical legal research method, using document and field studies. The data utilized is secondary data or library studies supplemented with primary data obtained through interviews with relevant sources. Qualitative analysis is used in the writing. The research findings indicate the need for regulations that provide legal certainty regarding the lessor's ownership of leased goods and mechanisms for maintaining such ownership, potentially at the level of a statute. The legal protection of the parties, particularly the lessor, currently relies heavily on the leasing agreements they enter into. The ownership function needs to be regulated explicitly, clearly, and comprehensively to ensure legal certainty for the lessor. Further, for such legal certainty, considerations should include a system for recording leased goods in an asset registry, a straightforward, cost-effective, and expeditious process for reclaiming leased goods if the lessee defaults, and the drafting of leasing agreements in the form of authentic deeds before a notary, containing complete and clear clauses to ensure legal certainty for the lessor.